2012
DOI: 10.1111/j.1440-1681.2012.05673.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of green tea catechins in various disease therapies: Progress and promise

Abstract: Green tea (from the plant Camellia sinensis), a beverage whose consumption started 5000 years ago in China, has important biological and pharmacological properties. The beneficial effects of green tea have been attributed to the presence of phenolic compounds that are powerful anti-oxidants and free iron scavengers. Of all the catechins found in green tea, namely (-)-epicatechin-3-gallate, (-)-epigallocatechin, (-)-epicatechin and (-)-epigallocatechin-3-gallate (EGCG), EGCG is the most abundant and powerful. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
76
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 81 publications
0
76
0
1
Order By: Relevance
“…Green tea catechins are receiving increasing attention for their potential palliative properties in lowering the risk of cardiovascular disease (Chacko et al, 2010) and as potential therapeutic intervention in cardiovascular diseases (Wolfram, 2007;Babu and Liu, 2008;Mak, 2012). Here, we report a novel mechanism of action for EGCG, the major catechin of green tea: EGCG modulates the function of Ca 2ϩ handling proteins in cardiac muscle, RyR2 Ca 2ϩ release channels, and NCX.…”
Section: Discussionmentioning
confidence: 99%
“…Green tea catechins are receiving increasing attention for their potential palliative properties in lowering the risk of cardiovascular disease (Chacko et al, 2010) and as potential therapeutic intervention in cardiovascular diseases (Wolfram, 2007;Babu and Liu, 2008;Mak, 2012). Here, we report a novel mechanism of action for EGCG, the major catechin of green tea: EGCG modulates the function of Ca 2ϩ handling proteins in cardiac muscle, RyR2 Ca 2ϩ release channels, and NCX.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the information regarding the effects of GT and GT polyphenols on several neurodegenerative disorders (reviewed in (Mak, 2012;Mandel et al, 2006), there is little information in literature about the use of GT to treat hemorrhagic stroke. In this study, using a collagenase model of ICH in rats, we show that GT treatment attenuates neuromotor deficit and striatum oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Catechins, a group of flavonoids, constitute around 30-45% of the solid GT extract (reviewed in (Mak, 2012)). The beneficial effects of tea consumption are probably due to its bioactive components (catechins and their derivatives), demonstrated to act directly as radical scavengers and to exert indirect antioxidant effects through activation of transcription factors and phase II antioxidant defense, thus modulating the cellular redox state (see review: Mandel et al, (2006).…”
mentioning
confidence: 99%
“…(+)-Catechin [(+)-C, Figure 1A], which is one of the major active components of green tea and edible plants [1] , displays the strongest antioxidant activity during human low-density lipoprotein (LDL) oxidation compared with other polyphenols [2] . It has been reported that the cytoprotective activity of catechins is mainly due to their radical-scavenging properties and iron-chelating effects in vivo [3] .…”
Section: Introductionmentioning
confidence: 99%